Cultural threads : transnational textiles today - Hemmings, Jessica (London : Bloomsbury, 2015)
"Cultural Threads considers contemporary examples of textile artists who work at the intersection of multiple cultural influences and use crafts as their vehicle. The roots of postcolonial theory lie in literature and have, in the past, been communicated through dense academic jargon. This book aims to break with the impenetrable rhetoric and instead show the rich visual diversity of craft and art that engages with multiple cultural influences. Postcolonial ideas about belonging to multiple cultures, which in reality result in a sense of connection to everywhere and nowhere simultaneously, are pertinent to society today more than ever. So too are the multiple, often overlooked, histories behind the objects that make up our material world. Many of these objects exist in an in-between world of their own, not wholly embraced by the establishments of art, nor functional objects in the conventional sense of craft. Cultural Threads is an exploration of modern textile art and its relationship with postcolonial culture; however, the postcolonial thinking examined here shares with craft an interest in the lived, rather than the purely theoretical, and as such is a very human account of these interactions between craft and culture"--
boek